The role of niche and regime intermediaries in building partnerships for urban transitions towards sustainability. Issue 2 (4th March 2022) - Ehnert, Franziska; Egermann, Markus; Betsch, Anna
ABSTRACT : The recent literature on intermediaries in urban sustainability transitions has studied their role as a translator between innovative niches and incumbent regimes. In urban sustainability transitions, intermediaries from both civil society and public institutions seek to bridge diverging world views and communicate innovative lessons learned back to the incumbent regime. How these intermediaries are embedded in local governance contexts and how the political dynamics inherent to urban sustainability transitions play out remains a research gap. As these transitions require political consensus-building, we explore the interaction between Transition Town Initiatives (TTIs) as niche intermediaries seeking to transform society from below, and regime-based transition intermediaries operating from above. In a comparative study of four German cities, we analyse why and how niche and regime intermediaries build partnerships for urban transitions towards sustainability. While Transition Town Hannover and Bluepingu in Nuremberg have successfully established partnerships with the municipalities, Transition Town Göttingen and Transition Town Kassel have struggled in their efforts to do so. These differences can be explained by the interactions between structural conditions, political priorities and institution-building, as well as the proficiency of transition intermediaries.